(untitled) (Jurnal Bina Praja, 2016)
The purpose of this study is to provide an overview of the system of electronic-based government or e-government in Indonesia. The development of e-government system in Indonesia is very important to answer the demands of globalization and modernization that are growing rapidly. E-government system is intended so that the governance is easier, faster, transparent, and effective. However, in its development, the implementation of e-government in Indonesia still needs various improvements. Information in this study is obtained from a variety of publications and documents related to the purposes of the study. The results of the study, among others, show that for technology resources,should the current government to allocate funds sufficient to meet the various devices related to the development of e-government. As for human resources, starting now, the government should have a commitment to provide informal education in the field of ICT in the state apparatus and society. To synchronize both strategies, it is necessary to build digital communities (digital society) throughout the region in Indonesia. The existence of digital society is considered not only able to develop better e-government system but also has an impact on economic acceleration. Other than those two things, the most important thing also requires commitment and strong leadership in developing e-government.